Evaluation of a new series of pyrazole derivatives as a potent epidermal growth factor receptor inhibitory activity QSAR modeling using quantum-chemical descriptors - Said, Ridha Ben (Journal of computational chemistry, 2021)
© 2021 Wiley Periodicals LLC.